Erfahrungsformate: Zur anthologischen Produktion von Authentizität in der bundesrepublikanischen Literatur um 1968, um 1980 und heute - Christopher Busch (Genealogy+Critique)
The article explores an important strand of German literature from ca. 1968 until today in terms of its inclination towards 'authentic communication', a feature that is part of the historiographical concepts of 'Neue Subjektivität' and 'Neue Sensibilität'. With Foucault and others it is argued, that authenticity can only be produced by acts of authentification and thus entails a power structure that needs to be unravelled in a theoretical framework which is sensitive to discourse analysis and its methodological ally, paratextual reading. The article thus focusses on anthologies as media of authenticity, media it is, that render specific powers to authors and/as editors. It is shown, that so called 'Neue Subjektivität'/'Neue Sensibilität' is a discursive effect produced by pedagogy and emancipatory groups (of the so called 'Alternativmilieu'). Its anthological re-discription in contemporary culture, however, should be conceived of as a means to re-introduce a genuine aesthetic that no longer can be described as merely communicative or non-experimental.